Convulsions in pregnancy-not always eclampsia role of neuro-imaging in diagnostic dilemma - Vijayasree, M.; Murali, GV (Health Renaissance, 2017)
Background: Convulsions in pregnancy is always considered and treated as Eclampsia unless otherwise proved. Eclampsia is associated with increased risk of maternal death varying from 1.8 % to 14 % in developed countries. Despite availability of Intensive care units and improved antenatal care, some women still die from Eclampsia. Cerebral complications are the major cause of death in eclampsia patients. Hypercoagulopathy of pregnancy is a high risk factor for these patients in respect to development of cerebro vascular thrombosis and ischaemic strokes. Eclampsia patients who are refractory to the routine treatment have been found to have various Central Nervous System pathological conditions amenable to the medical treatment. Objective: To study the neuro pathophysiology behind a seizure in pregnancy and to reduce the morbidity associated with it. To study the role of neuro-imaging in patients with convulsions in pregnancy not responding to treatment with magnesium sulphate (MgSo4). Methods: It was a prospective study design which included 50 antenatal mothers. All patients were admitted in the eclampsia room with history of convulsions and all of them were put on MgSo4 therapy and Antihyperertensives. The patients who were refractory to the treatment such as having recurrent convulsions despite therapy with MgSo4 were selected for neuro- imaging with Computed Tomography scan. Neuro-imaging was done using Phillips Tomoscan CT scanner where slices of 10-mm thickness were taken through the entire brain in the trans-axial plane. Abdomen shielding was done with lead shield to prevent radiation hazard in the antenatal period.The results were documented and analysed using appropriate statistical method. Results: The CT scanning report revealed: Cerebral oedema (30/50), Encephalopathy (10/50), Intra Cranial Haemorrhage (02/50) Cerebral infarction (01/50), Cortical venous sinus thrombosis (01/50), Tuberculomas (01/50), Neurocysticercosis (01/50) and Hydrocephalus (01/50). Three patients out of 50 had normal CT scan report. Conclusion: Patients with convulsions in pregnancy who were refractory to the treatment with MgSo4 and Antihypertensives have been found to have very significant and morbid CNS pathological conditions. Neuro imaging in these patients have done a pivotal role in identifying the abnormality and rectifying it with medical means which had definitely improved patients conditions and have reduced morbidity and mortality. Health Renaissance 2015;13 (3): 144-151